Passive treatment (wetland) in mine waters of the Cía. de Minas Buenaventura S.A.A - Méndez Quincho, Leonor Cramen (2001)
The city of Puno was founded in 1668, currently it has a population of more than 100,000 inhabitants. The wastewater from the city of Puno without treatment has been discharged into the Inner Bay of the same name until in 1972, the wastewater treatment plant was built by means of stabilization ponds on Espinar Island. The treated waters are discharged into the Inner Bay of Puno. About 26% of the wastewater from the city of Puno is treated at the aforementioned plant, while 74% are discharged into the Inner Bay without any treatment. The consequence of the discharge of treated and untreated wastewater into the Inner Bay is the growth of the Lemna floating plant known as duckweed. In view of this situation, the Lake Titicaca Binational Special Project (PELT), with the advice of the Japanese Technical Cooperation Agency (JICA), began to carry out water quality studies of the Inner Bay of Puno from January 1999.